The role of dung beetles in seed dispersal in an arid environment - M. Belén Maldonado; Alejandro M. Serrano; Natacha P. Chacoff; Diego P. Vazquez (Ecología Austral, 2023)
Dung beetles can influence seedling emergence and survival. However, the direction and magnitude of this effect will depend on the functional traits of the dung beetle community and on the prevailing environmental conditions. We studied the role of dung beetles in seed dispersal of Prosopis flexuosa DC. in an arid environment. We conducted an experimental study to assess how different dung beetle species differ in their effectiveness as secondary seed dispersers. To evaluate this question, we selected four species belonging to three functional groups: lifters, tunnelers, and rollers. Dung beetles removed 0.7%-7.5% of the seeds embedded in cow dung. The net effect of beetles on seedling emergence and survival varied markedly among species: Malagoniella puncticollis (roller) had neutral effects on seedling emergence and positive in their survival. Sulcophanaeus imperator, Digitonthophagus gazella (tunneler) and Eucranium arachnoides (lifters) species had positive effect on seedling emergence. However, the effect of S. imperator on seedling survival was negative, and those of D. gazella and E. arachnoides, neutral. Our results indicate that although dung beetles remove few seeds of P. flexuosa, their main role consisted in producing changes in micro-environmental conditions for the seeds that remained in the dung pile.